Relação entre oncentração sérica e consumo dietético habitual de vitamina A versus valores de proteína C reativa em idosos: um estudo de base populacional - Nascimento, Christiane Carmem Costa do (2010)
The aging population is one of the main results of demographic trends during the twentieth century. Anatomical and functional changes typical of aging can lead to specific deficiencies of nutrients. Vitamin A plays a key role in numerous physiological functions and the serum retinol concentrations are related to organic resistance against infections. Researches aimed at the diagnosis of vitamin A deficiency should include the analysis of serum concentrations of inflammatory markers in acute phase such as C-reactive protein in order to enable better expression of the vitamin A status. This study aimed to evaluate the importance of the habitual dietary vitamin A intake on the serum retinol concentrations in elderly people. This is a cross-section population-based epidemiological study conducted in João Pessoa / PB / Brazil in the period from 2008 to 2009 with 212 individuals between 60 and 90 years of age, from both genders. Data were collected for habitual food intake, retinolemia, C - reactive protein (CRP), and socioeconomic and anthropometric aspects. The mean vitamin A intake was 1643.40 μg RAE / day (p25 = 1112.20 - p75 = 2430.80). The average serum retinol concentration was 1.91 ± 0.68 μmol/L. There was no correlation between CRP concentration and serum retinol (r = 0.061 / p = 0.424), nor with habitual dietary retinol consumption (r = 0.000 / p = 0.932). However, there was a direct relationship between consumption and serum retinol levels (r = 0.173 / p = 0.025). Only 3,98% (IC95% 6,88 1,08) of subjects had inadequate serum retinol concentrations (<1.05 mmol / L), and 12.4% (CI 95% 17.36 to 7.44) Inadequate vitamin A intake (<625μg, males and <500μg, females). The elderly population from the municipality of João Pessoa / Paraíba / Brazil revealed a proper retinolemia status and habitual vitamin A intake and no correlation was found between CRP concentration and dietary serum retinol, probably because the sample was composed of elderly patients with no acute infection or absence of decompensated chronic diseases. The present study emphasizes the influence of dietary preformed vitamin A intake on the serum retinol concentrations, which seems to be an affective strategy to combat vitamin A deficiency in this population.